Mortality of Three Major Gynecological Cancers in the European Region: An Age–Period–Cohort Analysis from 1992 to 2021 and Predictions in a 25-Year Period - Yanxue Lian; Pincheng Luo (Annals of Global Health)
Background: The European region is marked by pronounced disparities in healthcare access, socioeconomic conditions, and cancer control policies, which influence the mortality trends of gynecological cancers across countries and may persist or intensify in the coming decades. Objective: This study analyses mortality trends of three main gynecological cancers, including ovarian, uterine, and cervical cancers in the European region from 1992 to 2021 and projects rates for the next 25 years to support targeted public health interventions. Methods: Data from the Global Burden of Disease 2021 were used. An age‑period‑cohort (APC) model estimated overall annual percentage changes in mortality (net drifts), local drifts, and age/period/cohort effects for gynecological cancers in the European region. A log‑linear APC model projected mortality and age‑standardized mortality rates (ASMRs) from 2022 to 2046. Findings: Over the past three decades, the European region has had some of the highest mortality rates globally for ovarian and uterine cancers, while trends for cervical cancer have been more favorable. Overall, gynecological cancer mortality declined, though rates increased with age, but period and cohort effects weakened. Ovarian cancer mortality decreased in 17 of the 44 countries studied, while remaining stable in the others. Uterine cancer mortality rose in three countries, with the most pronounced increase observed in Italy. Cervical cancer mortality declined in 32 countries, with Italy being the only country to show an upward trend. Forecasts indicate a steady increase in uterine cancer deaths over the next 25 years, with slight decreases in ASMR, while ovarian cancer and cervical cancer deaths and ASMRs are projected to decline. Conclusion: Despite overall progress in reducing gynecological cancer mortality, significant disparities remain, particularly among older populations and in certain countries such as Italy. Projections indicate a rise in uterine cancer mortality, highlighting the urgent need to strengthen early screening, preventive measures, and equitable healthcare strategies to reduce future disease burden.